Multiple-family group intervention programming to improve mental health of adolescents living with HIV/AIDS in Ghana: An implementation science study protocol - Dorothy Serwaa Boakye; Samuel Adjorlolo (PLoS ONE, 2025)
Background Adolescents living with HIV/AIDS in sub-Saharan Africa face a disproportionate burden of mental health challenges and suboptimal antiretroviral therapy (ART) adherence, which can have significant consequences for their overall health and well-being. While multiple family group therapy (MFGT) has shown promise in improving outcomes for ALHIV in other settings, the intervention is yet to be wholly adapted and evaluated in the Ghanaian context. This study aims to adapt, pilot, and evaluate a multiple family group therapy (MFGT) intervention to improve mental health and ART adherence among adolescents living with HIV/AIDS in Ghana. Methods A total of 80 ALHIV (aged 10–19 years at enrollment) will be recruited from two HIV clinics and each clinic will be randomized to one of two study conditions (MFGT group and control group). The study will be conducted in three phases: 1) Adaptation Phase – Qualitative data collection through focus group discussions and in-depth interviews with key stakeholders (adolescents, caregivers, community leaders and healthcare providers) to inform the adaptation of the MFGT intervention for the Ghanaian context; 2) Pilot Implementation Phase – Quantitative assessments (PHQ-9, GAD-7, Wilson’s 3-item adherence scale, FAD, Berger HIV Stigma Scale) and qualitative data collection (focus groups, interviews) to evaluate the feasibility, acceptability, and preliminary effectiveness of the adapted MFGT intervention; and 3) Evaluation Phase – Continuation of the quantitative and qualitative data collection, as well as a cost-effectiveness analysis, to assess the long-term impact, sustainability, and scalability of the MFGT intervention. Expected Outcomes The study will provide valuable insights into the feasibility, acceptability, and effectiveness of the adapted MFGT intervention in improving mental health and ART adherence among adolescents living with HIV/AIDS in Ghana. The findings will inform the development of culturally relevant and sustainable strategies to support this vulnerable population, with potential implications for similar interventions in other sub-Saharan African contexts. Ethics and Dissemination The study has obtained necessary ethical approvals from the Ghana Health Service Ethics Review Committee and relevant health authorities, and will follow international research guidelines. Findings will be disseminated through peer-reviewed publications, conference presentations, and clinical trial registry, with an emphasis on open-access formats to maximize accessibility. Protocol Registration in Clinical Trials.gov (NCT06701942). Date of trial registration 24 November, 2024.